Pengendalian Persediaan Bahan Baku Petis Udang dengan Menggunakan Metode Economic Order Quantity (Eoq) di Ud. Agung Jaya - Rufaidah, Anik; Rosyidi, Moh. Ririn; Suparno, Suparno (Universitas Teuku Umar, 2024)
Raw material inventory is very important for companies. UD. Agung Jaya is a company that operates in the food sector, namely Petis Udang. Problems at UD. Agung Jaya has raw material stock problems, namely a shortage or excess of raw materials. The aim of this research is to help optimize UD costs of UD. Agung Jaya. This research uses raw material purchase data for shrimp heads, sugar, and flour which is processed by forecasting calculations for 12 periods or 1 year into the future using the single exponential smoothing (SES) time series forecasting method. The aim is to determine the need for raw materials so that there are no shortages or excesses of raw materials during the ongoing production process, and the efficiency of raw material needs in this research. The results of the research show that the raw material for shrimp heads has a mape error value of 24, sugar has a mape error value of 24, and flour has a mape error value of 26.1. Furthermore, the raw material decomposition method for shrimp heads has a mape error value of 15, sugar has a mape error value of 15, and flour has a mape error value of 16.42. The second result of forecasting shows that the decomposition method obtains a smaller mape value or the lowest error value. This research also uses the Economic Order Quantity (EOQ) method in the 2022-2023 period with raw material yields of 515.28 kg of shrimp heads, 488.54 kg of sugar and 188.09 kg of flour.